Diagnostic performance of a novel ESAT6-CFP10 skin test for tuberculosis infection in school tuberculosis outbreak in China - Lu, Peng; Xu, Jingjing; Wang, Rong; Gong, Xiaona; Liu, Qiao; Ding, Xiaoyan; Lu, Wei; Zhu, Limei (Frontiers in Public Health, 2024)
Background The ESAT6-CFP10 (EC) skin test is recommended by the World Health Organization for latent tuberculosis infection (LTBI). However, it is still unknown how the EC skin test performs in students during a school tuberculosis outbreak. Methods We conducted an epidemiological investigation to assess the performance of the EC skin test in this high-risk population. Results A total of 9 active student patients were confirmed in the same class as the index case, with an incidence rate of 18.0% (9/50). Among the 50 close contacts, 14 (28%) were over 15 years old and had a chest X-ray (CXR), and none of them had abnormal CXR findings. The rates of positive tuberculin skin test (TST) ≥ 5 mm and < 10 mm, ≥ 10 mm and < 15 mm, and ≥ 15 mm were 12.0% (6/50), 16.0% (8/50), and 10.0% (5/50), respectively. On the second screening, 44 students with the same class as the index case had the EC skin test, of which 31 (70.5%) had positive EC tests. All patients had negative sputum smear results, of whom 4 (44.4%) had positive Xpert results; three had a TST induration diameter between 5 mm and 10 mm, but all of them had an EC diameter > 15 mm; 5 (55.6%) had abnormal CXR results, but all the confirmed patients had abnormal CT results; Except for four cases that were diagnosed by Xpert, the remaining five were confirmed by CT scan. Conclusion The novel EC skin test performed well in students during the school tuberculosis outbreak. In some special conditions, such as when the index case is bacteriologically positive for tuberculosis and the rate of LTBI is higher than the average for the local same-age group, secondary screening is recommended 2–3 months after the first screening. Furthermore, we cannot ignore the role of CT in the diagnosis of early student tuberculosis.